Dynamic rupture processes inferred from laboratory microearthquakes. Issue 6 (11th June 2016) - Passelègue, François. X.; Schubnel, Alexandre; Nielsen, Stefan; Bhat, Harsha S.; Deldicque, Damien; Madariaga, Raùl
Abstract: We report macroscopic stick‐slip events in saw‐cut Westerly granite samples deformed under controlled upper crustal stress conditions in the laboratory. Experiments were conducted under triaxial loading ( σ 1 > σ 2 = σ 3 ) at confining pressures ( σ 3 ) ranging from 10 to 100 MPa. A high‐frequency acoustic monitoring array recorded particle acceleration during macroscopic stick‐slip events allowing us to estimate rupture speed. In addition, we record the stress drop dynamically and we show that the dynamic stress drop measured locally close to the fault plane is almost total in the breakdown zone (for normal stress >75 MPa), while the friction f recovers to values of f > 0.4 within only a few hundred microseconds. Enhanced dynamic weakening is observed to be linked to the melting of asperities which can be well explained by flash heating theory in agreement with our postmortem microstructural analysis. Relationships between initial state of stress, rupture velocities, stress drop, and energy budget suggest that at high normal stress (leading to supershear rupture velocities), the rupture processes are more dissipative. Our observations question the current dichotomy between the fracture energy and the frictional energy in terms of rupture processes. A power law scaling of the fracture energy with final slip is observed over 8 orders of magnitude in slip, from a few microns to tens of meters. Key Points: Dynamic stress change during laboratory earthquakes Complete capture of the weakening processes Scaling with natural earthquakes